1997
DOI: 10.1128/jvi.71.8.6194-6199.1997
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of the UV-damaged DNA-binding protein with hepatitis B virus X protein is conserved among mammalian hepadnaviruses and restricted to transactivation-proficient X-insertion mutants

Abstract: We carried out a comparative analysis of several proposed host protein partners of the human hepatitis B virus X protein (HBx) using both the GAL4-and the LexA-based yeast two-hybrid system. We showed that the interaction of HBx with the UV-damaged DNA-binding protein (UVDDB) is positive in both yeast systems, detectable in cotransfected human cells, conserved by rodent hepadnavirus X proteins (known to transactivate in human cells), and tightly correlated with the transactivation proficiency of X-insertion mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
41
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(43 citation statements)
references
References 38 publications
(42 reference statements)
2
41
0
Order By: Relevance
“…In the present study, this method, combined with mass spectrometric analysis, was introduced to search for the HBx‐binding molecules in Huh‐7 hepatoma cells, and a total of five proteins were identified. Among these, DDB1 [Sitterlin et al, 1997; Leupin et al, 2005] and HSP70 [Zhang et al, 2005] were also reported previously to interact with HBx, which validated the present methods. However, the results also showed that there was much non‐specific binding of non‐FLAG tagged proteins from the Huh‐7 lysate.…”
Section: Discussionsupporting
confidence: 82%
“…In the present study, this method, combined with mass spectrometric analysis, was introduced to search for the HBx‐binding molecules in Huh‐7 hepatoma cells, and a total of five proteins were identified. Among these, DDB1 [Sitterlin et al, 1997; Leupin et al, 2005] and HSP70 [Zhang et al, 2005] were also reported previously to interact with HBx, which validated the present methods. However, the results also showed that there was much non‐specific binding of non‐FLAG tagged proteins from the Huh‐7 lysate.…”
Section: Discussionsupporting
confidence: 82%
“…Viral load has been shown to be one of many clinical variables that impact the therapeutic outcomes and natural history of chronic HBV infection [4,15]. As with most infectious agents, both host and viral factors have been shown to affect the risk of chronic infection and the severity of clinical disease [16][17][18][19][20][21][22][23]. As an effective statistical tool with which to accurately assess HBV DNA measurements, MMM is able to provide clinicians with statistically normalized viral load determinations, which can allow one to focus on the host and viral factors in the design and monitoring of individualized therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, interaction of wtHBx with DDB1 may affect the integrity of the genome by modulating CDT1 degradation. wtHBx also interacts with single stranded DNA and a series of DNA repair proteins, resulting in inefficient repair of damaged cellular DNA . By blocking DNA repair, wtHBx may facilitate the fixation of mutations and play a role in hepatocarcinogenesis.…”
Section: Hbx: a Viral Proto‐oncogene Evolving In The Course Of Multismentioning
confidence: 99%